The Impact of Kishk Components on the Physiochemical and Sensory Properties of Kishk - Zainulabiden, Mohammad wajeeh; Ahmed, Tara Abdul-Rahman; Rostam, Awaz Omar (Sulaimani Journal for Pure and Applied Sciences, 2015)
Two varieties of wheat, Bakrajo (durum) and Aras (bread wheat) were used to prepare two sizes of burgul which used as a components in Kishk mixture. Kishk was prepared in two groups of mixtures: 1:3 and 1:4 burgul : doogh (yogurt drink) with or without malt (0.5% on flour basis) Using course burgul granules (>1000μ) decreased gelatinization temperature and increased Amylograph maximum viscosity compared to use fine burgul granules (< 350μ) and malt addition, which indicated to present of ungelatinized starch in dried kishk. Results showed that kishk powder flowability (Carr index) depended on their agglomeration more than it’s depending on any components of kishk mixtures. Sensory evaluation showed that an increasing in kishk odor, taste and color took place when 0.001 part of malt was added.
Keywords: Kishk,Burgul; Amylograph; Carr Index